2017
DOI: 10.3201/eid2309.170168
|View full text |Cite
|
Sign up to set email alerts
|

Indication of Cross-Species Transmission of Astrovirus Associated with Encephalitis in Sheep and Cattle

Abstract: We report the identification of a neurotropic astrovirus associated with encephalitis in a sheep. This virus is genetically almost identical to an astrovirus recently described in neurologically diseased cattle. The similarity indicates that astroviruses of the same genotype may cause encephalitis in different species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 11 publications
4
68
0
Order By: Relevance
“…Recently, neurotropic astrovirus associated with encephalitis was identified in a sheep. Interestingly, the similarity found among this strain and a astrovirus described in neurologically diseased cattle, indicates that astroviruses of the same genotype may cause encephalitis in different species [10]. So far, AstVs have been detected in over than 80 avian and mammalian host species [11].…”
Section: Introductionmentioning
confidence: 76%
“…Recently, neurotropic astrovirus associated with encephalitis was identified in a sheep. Interestingly, the similarity found among this strain and a astrovirus described in neurologically diseased cattle, indicates that astroviruses of the same genotype may cause encephalitis in different species [10]. So far, AstVs have been detected in over than 80 avian and mammalian host species [11].…”
Section: Introductionmentioning
confidence: 76%
“…Altogether, these findings suggest that there are probably other still unrecognized divergent astroviruses with clinical implications beyond gastroenteritis in humans and animals. The potential for cross-species transmission is high (43,44), and the increasing number of descriptions of nonenteric severe clinical manifestations in animals, especially neurologic involvement, should prompt us to validate appropriate systems to study the pathogenicity of astroviruses. Among the novel human astroviruses, a cell culture system has been recently described for VA1 (45).…”
mentioning
confidence: 99%
“…Another study suggested a common ancestor between the MLB clade and astrovirus identified in rats 21 . These data suggest a cross-species transmission 22,23 , which could have occurred long time ago. Sequences of novel HAstVs have been found in human stools of individuals with diarrhea 15,[24][25][26] , but also in asymptomatic healthy controls 27,28 ; unfortunately, the two latter reports have contradictory results in their case-control study, especially for MLB1, which so far is the most common.…”
mentioning
confidence: 68%